Exceptional long-term survival in an adult with advanced classic biphasic pulmonary blastoma: a case report and literature review - Li, Jun; Chen, Si; Liu, Qiliang; Li, Ming (Frontiers in Oncology, 2026)
BackgroundPulmonary blastoma (PB) is an exceedingly rare and aggressive primary lung malignancy. Classic biphasic pulmonary blastoma (CBPB), a subtype, is associated with a historically poor prognosis, particularly in advanced stages. There is no standard treatment for advanced CBPB, and reports of long-term survival are exceptionally rare. We present a case of prolonged disease-free survival in an adult with stage IIIC CBPB and review contemporary long-term survivors to identify prognostic factors.Case presentationA 32-year-old female presented with cough and dyspnea. Imaging revealed a large mass in the left upper lobe with mediastinal and supraclavicular lymph node involvement, leading to a diagnosis of stage IIIC CBPB. The patient received six cycles of neoadjuvant chemotherapy with ifosfamide plus epirubicin (IFO + EPI) and achieved a partial response. She subsequently underwent left upper lobectomy and lymph node dissection. Due to dense adhesion of mediastinal lymph node station 5 to the aortic arch, phrenic nerve, and vagus nerve, complete resection was not feasible, resulting in R2 resection (macroscopic residual disease). Postoperatively, she completed adjuvant chemoradiotherapy (one cycle of IFO + EPI, concurrent radiotherapy 54 Gy combined with docetaxel plus carboplatin, and two cycles of docetaxel plus cisplatin). As of July 2025, the patient has remained disease-free for more than six years post-diagnosis, demonstrating exceptional long-term survival.ConclusionThis case highlights that aggressive multimodal therapy, including neoadjuvant chemotherapy, surgical resection, and adjuvant radiotherapy, can lead to long-term survival in advanced CBPB patients. A literature review (from 2000 to present) revealed 13 CBPB patients surviving > 3 years, with 5 of them surviving ≥ 5 years. Most of these patients underwent surgery and multimodal treatment. Aggressive local therapy for recurrent disease and antiangiogenic agents and immunotherapy represent promising strategies to improve outcomes in this rare malignancy.